FAKTOR RISIKO TERJADINYA AKNE VULGARIS PADA SISWA - SISWI KELAS XII SMA HARAPAN 1 MEDAN - FITRI HAFIANTY; DIAN ERISYAWANTY BATUBARA; FEBRINA DEWI PRATIWI LINGGA (JURNAL ILMIAH SIMANTEK, 2021)
Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicles which generally occurs in adolescence and canheal itself. This study aims to determine the risk factor expect acne vulgaris through several characteristics in class XIIstudens. The research method is a descriptive cross sectional study with a sample collection technique is consecutivesampling. The sample in this study is class XII students in high school of Harapan 1 Medan. This study used questionnairesand direct examination on the face and neck area to diagnose acne vulgaris in high school of Harapan 1 Medan. The resultsof the study with the majority of patients with acne vulgaris have mild degree acne (63.5%), have families who suffer fromacne vulgaris (81%), the type of food consumed is bread with butter (17.5%), normal skin type ( 42.5%), irregularly cleaningthe face (78.8%), cleaning the face <2x daily (82.5%) using special facial washing soap (87.5%), not using any cosmetics(37.5%), acne occurs before or during menstruation (70.6%), stress is quite severe (81%). From the results of this study, themost influential risk factors for the appearance of acne vulgaris are family history (81%), stress factors (81%), irregular facialcleaning (78.8%), cleaning of the face <2x a day (82.5%) and acne occurs before or during menstruation (70,6%).